Status Penglihatan Pasien Makroadenoma Hipofisis Pasca Bedah Transphenoid - Reny Setyowati; Adiguno Suryo Wicaksono; Rahmat Andi Hartanto; Indra Tri Mahayana; Suhardjo Prawiroranu (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2019)
AIM: The main aim of surgery in pituitary macroadenoma are restoration of visual acuity and visual field defects by decompression of the optic chiasm. Pituitary macroadenoma has slow growth pattern. This study describes the visual status of patients with pituitary macroadenoma and the post operative results. METHODS: Retrospective, descriptive interventional study of patients with pituitary adenoma underwent transphenoid surgery at Dr Sardjito General Hospital, Yogyakarta. RESULTS: There were 7 patients age 29-65 years old, mean age was 42 years old, consist of 3 male and 4 female and were followed-up varies between 1 until 6 months. There was history of previous transphenoid surgery in 1 patients. Duration of patient’s complaint varies between 1 until 36 months and the mean duration was 12 months. In 6 patients there were bitemporal hemianopia and 1 patients had general depression visual field defect. Visual acuity pre operative was between 0,003 until 1,0 , and the mean visual acuity was 0,1 (right eye) and 0,18 (left eye). Visual acuity post operative was between no light preception until 1,0 , and the mean visual acuity was 0,27 (right eye) and 0,19 (left eye) but there were no statistically significant differences. Fundus examination reveal optic atrophy in all patients. CONCLUSION: Transphenoidal surgery is the treatment of choice in patients with pituitary macroadenoma. Prolonged duration of symptoms and delay of surgery may impact the visual status KEYWORDS: Visual status, visual field defect, pituitary macroadenoma, transphenoid surgery, post operative